Determinants of Micro and Small Business Financing In Sharia Commercial Banks In Indonesia - Uus Ahmad Ahmad Husaeni (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to examine and analyze the effect of bank size, efficiency, liquidity, and BI rate on MSME financing at Sharia Commercial Banks (BUS) in Indonesia. Research data in the form of secondary data obtained from the official website of Bank Indonesia. The data is analyzed using multiple linear regression analysis. Before the information is further explored, several classic assumption tests are performed, including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Based on testing the hypothesis using the t-test it was concluded that bank size has a positive effect on MSME financing, efficiency does not affect MSME financing, liquidity has a positive impact on MSME financing, and the BI rate has a positive impact on MSME financing